2020
DOI: 10.1111/cen.14338
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of adrenal masses by [18F]FDG PET/CT: Changing tactics

Abstract: Context[18F]FDG PET/CT improves adrenal tumour characterization. However, there is still no consensus regarding the optimal imaging biomarkers of malignancy.ObjectivesTo assess the performance of Tumour standardized uptake value (SUV)max:Liver SUVmax for malignancy‐risk and to build and evaluate a prediction model.Design/MethodsThe cohort consisted of consecutive patients with adrenal masses evaluated by [18F]FDG PET/CT. The gold standard for malignancy was based on histology or a multidisciplinary consensus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…This cut-off applied to our entire population showed Sn, Sp, PPV, and NPV of 100%, 87%, 73%, and 100% respectively, con rming the two previous researches [1,22]. The proposed 1.5 cut-off in our population agreed with the diagnosis according to the gold standard in most of the cases (38 cases; 90.5%); the 4 discordant lesions with a SUVratio > 1.5 and a non-malignant diagnosis were 2 non-functioning adenomas, 1 hyperplasia, and 1 pheochromocytoma.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This cut-off applied to our entire population showed Sn, Sp, PPV, and NPV of 100%, 87%, 73%, and 100% respectively, con rming the two previous researches [1,22]. The proposed 1.5 cut-off in our population agreed with the diagnosis according to the gold standard in most of the cases (38 cases; 90.5%); the 4 discordant lesions with a SUVratio > 1.5 and a non-malignant diagnosis were 2 non-functioning adenomas, 1 hyperplasia, and 1 pheochromocytoma.…”
Section: Discussionsupporting
confidence: 90%
“…As a second step, we tried to calculate the best cut-off in our population, reaching the same results of previous studies [1,22]. In particular, the best cut off for SUVratio was 1.55 in the whole population (with or without pheochromocytomas), and 1.49 excluding patients with metastases and pheochromocytomas.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Using a ratio of adrenal tumor standardized uptake value maximum (SUV max ) to liver SUV max newer studies have demonstrated promising results. For instance, a recent study assessed this new biomarker in 64 patients [45]. Using a cutoff of 1.5 the tumor to liver SUV max demonstrated a sensitivity of 90% and specificity of 93% in identifying malignant lesions.…”
Section: Identifying Malignancymentioning
confidence: 99%